Management of ureteropelvic junction obstruction in children—a roundtable discussion. Issue 4 (August 2019) - Gopal, M.; Peycelon, M.; Caldamone, A.; Chrzan, R.; El-Ghoneimi, A.; Olsen, H.; Leclair, M.-D.; Stillebroer, A.; MacDonald, C.; Tonnhofer, U.; Strasser, C.; Adam, A.; et al.
Summary: The investigation, management and follow-up of paediatric ureteropelvic junction obstruction is not standardized. The Young Pediatric Urology Committee of the European Society of Pediatric Urology interviewed five experts in the field on various aspects of management and compared this with published literature.